2017
DOI: 10.1016/s0140-6736(16)31714-7
|View full text |Cite|
|
Sign up to set email alerts
|

Relation between resting amygdalar activity and cardiovascular events: a longitudinal and cohort study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
385
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(445 citation statements)
references
References 41 publications
21
385
2
5
Order By: Relevance
“…This suggests the possibility of an identifiable brain phenotype or brain biomarker that reflects stress‐related CVD risk. This possibility agrees with recent findings demonstrating that brain activity linked to psychological stress forecasts clinical CVD events 59. Accordingly, the present findings are relevant not only for furthering the understanding the neural bases of individual differences in cardiovascular stress physiology, but also for understanding the neural pathways that mechanistically link stressful experiences and CVD in at risk and clinical populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests the possibility of an identifiable brain phenotype or brain biomarker that reflects stress‐related CVD risk. This possibility agrees with recent findings demonstrating that brain activity linked to psychological stress forecasts clinical CVD events 59. Accordingly, the present findings are relevant not only for furthering the understanding the neural bases of individual differences in cardiovascular stress physiology, but also for understanding the neural pathways that mechanistically link stressful experiences and CVD in at risk and clinical populations.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, future studies may be able to identify individuals who more strongly exhibit a multivariate brain pattern that predicts clinically meaningful outcomes (eg, disease progression, new events, etc) 52. In a recent and foundational illustration of the plausibility of such a brain‐based approach to predict CVD risk, Tawakol et al59 demonstrated that elevated levels of basal metabolic activity within the amygdala predicted future CVD events above and beyond conventional CVD risk factors. An open question is whether multivariate and network‐based approaches used in the present study would add to the predictive value of such single‐region–based approaches and complement conventional CVD risk‐prediction approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This first study to link regional brain activity to subsequent cardiovascular disease illustrated findings providing novel insights into the mechanism that how emotional stressors lead to cardiovascular disease in human beings [41]. These procedures may perform as a novel tool for evidence-based medicine to evaluation the whole body effectiveness of the programs (in CAM) mentioned above.…”
Section: Relaxation Responsementioning
confidence: 95%
“…The prevalence of these factors is higher in women during their lifetime with a different impact on IHD than in men. Emotional activity has recently been shown to activate arterial inflammation, which is importantly involved in functional IHD [10]. Chronic psychological stress inhibits many functions of the immune system, which may enhance a higher susceptibility to endothelial dysfunction and vasospasm.…”
mentioning
confidence: 99%